Dynamics of Reasonableness and Fairness in a Pluralistic Legal System: Perspectives from Adat, Islamic and Civil Inheritance Law - Annida Aqiila Putri; Bart Jansen (Universitas Airlangga, 2021)
Reasonableness and fairness are keystones of law. They are implemented broadly and important doctrine for civil law. However, the open nature of reasonableness and fairness allow various interpretations, influenced by the legal system, legal tradition, jurisprudence or measured on a case per case basis. Indonesia recognizes more than one kind of a legal system, making it a legal pluralist State. This article aims to describe the dynamics of the reasonableness and fairness principle within a pluralistic legal system. Indonesian inheritance laws use three different legal systems: Adat, Islam, and civil law, each provides distinctive perspectives of reasonableness and fairness. These differences may lead to a clash of interpretation or it may leave a wide room of discretion for the judges. Court judgments are analyzed to examine the implementation of such dynamics in practice. Finally, the outcome of the paper concludes whether the differences shall be embraced or whether there is a need to agree upon what is ‘reasonable’ and ‘fair’.